(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Butyrina M. V. Particularities of the design and development of tests for teaching knowledge control The article describes the current problems of the organization of control test for students’ ‘knowledge of higher educational institutions, described the objectives and types of teacher testing, development and studied the sequence requirements for the establishment and application of tests, investigated the advantages and disadvantages of the test control knowledge as a way to control the students’ knowledge.